Virtual reality for design and site planning in construction projects: Advantages and barriers - Espinoza, Marck S. Regalado; Varillas, Christopher J. Nunez; Crosostomo, Oswaldo D. Leon; Zamora, Emily N. Rios (2023 Congreso Internacional de Innovación y Tendencias en Ingeniería (CONIITI), 2023)
Construction projects are important for the development of any society. However, it is very common that they present different problems, such as delays, rework, exposure to high-risk activities, changes in the project, among others, which causes the industry to be increasingly inefficient. Therefore, different technologies have been incorporated in this industry to correct these deficiencies, within which in this research the use of virtual reality is analyzed. To this end, we begin with a bibliographic review of 28 scientific articles related to the subject, which allowed us to identify 5 advantages that would lead to the implementation of this technology in the design and planning phases of civil works. Also, 6 barriers were identified that would limit its implementation in a certain study area, such as in a country or city. Then, to rank them, a survey was designed based on the AHP (Analytic Hierarchy Process) method, which ranks them in pairs. Peru was taken as a study example, and a total of 37 professionals in the construction industry were surveyed. The main advantages of this technology are design reviews (29.7%), the complement with augmented reality (18.3%), and interactive virtual display (17.5%). Similarly, the main barriers are the high costs of the technology (23.8%), the need for skilled personnel (22.1%), and the uncertainty about new technologies (16.4%). It should be noted that this methodology can be replicated in any city or country where it is desired to analyze the advantages and barriers of implementing virtual reality in the construction industry, after adapting it to the local context and with the opinions of local experts.